2012
DOI: 10.1100/2012/520632
|View full text |Cite
|
Sign up to set email alerts
|

General and Electrophysiological Toxic Effects of Manganese in Rats following Subacute Administration in Dissolved and Nanoparticle Form

Abstract: In an attempt to model occupational and environmental Mn exposures and their possible interaction, young male Wistar rats were exposed to Mn by oral administration in dissolved form (MnCl2 ·4H2O, 14.84 and 59.36 mg/kg b.w.) and by intratracheal application of MnO2 nanoparticles (2.63 mg/kg b.w.). After 3 and 6 weeks oral, or 3 weeks oral plus 3 weeks intratracheal, exposure, general toxicological, and electrophysiological tests were done. Body weight gain was significantly reduced after 6 and 3 plus 3 weeks ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
1
18
0
4
Order By: Relevance
“…Подтверждением недостаточности антиоксидантных процессов является сни-жение уровня Cu/ZnСОД и ОАС в сыворот-ке крови. По результатам проведенного ис-следования установлено, что клетками-мишенями для водной суспензии нанодис-персного MnO при пероральном поступле-нии, так же как и при ингаляционной экс-позиции, являются астроциты и мембраны нейронов [8,10,13]. В случае перорального поступления это может быть обусловлено выраженной способностью нанодисперс-ных частиц MnO, как и других металлов, проникать из желудочно-кишечного тракта в кровь.…”
Section: а бunclassified
See 1 more Smart Citation
“…Подтверждением недостаточности антиоксидантных процессов является сни-жение уровня Cu/ZnСОД и ОАС в сыворот-ке крови. По результатам проведенного ис-следования установлено, что клетками-мишенями для водной суспензии нанодис-персного MnO при пероральном поступле-нии, так же как и при ингаляционной экс-позиции, являются астроциты и мембраны нейронов [8,10,13]. В случае перорального поступления это может быть обусловлено выраженной способностью нанодисперс-ных частиц MnO, как и других металлов, проникать из желудочно-кишечного тракта в кровь.…”
Section: а бunclassified
“…При этом на-блюдается незначительное угнетение мито-хондриальной деятельности, происходит дозозависимое уменьшение концентрации дофамина и его метаболитов: дигидрокси-фенилуксусной кислоты и гомованилино-вой кислоты. Данный процесс сопровожда-ется многократным увеличением АФК [11] и проявляется у экспериментальных жи-вотных нейродегенеративными наруше-ниями уже через 2-3 недели экспозиции [14,19], активацией протеолитического рас-щепления, опосредованного каспазой-3 и про-теинкиназой Сδ (ферментами, участвующи-ми в процессах апоптоза, некроза и воспа-лительных процессах), а также активацией цикла фосфорилирования [5,9,10,13]. По данным других авторов, при интраназаль-ном введении наночастиц оксида марганца (IV) в дозе 2,63 мг/кг массы тела в течение 6 недель у крыс наблюдается появление нейротоксичности по увеличению относи-тельного рефрактерного периода хвостового нерва [17].…”
unclassified
“…This process is accompanied by a slight inhibition of mitochondrial activity and a dose-dependent decrease in the concentration of dopamine and its metabolites: dihydroxyphenylacetic acid and homovanillic acid. This process is accompanied by a multiple increase in the ROS [11] and presents in experimental animals in the form of neurodegenerative disruptions after 2-3 weeks of exposure [8,13], activation of proteolytic cleavage mediated by caspase-3 and protein kinase Sδ (enzymes involved in the processes of apoptosis, necrosis and inflammatory processes), as well as phosphorylation of the activation loop [5,10,12,19]. According to other authors, intranasal introduction of manganese dioxide nanoparticles (IV) to rats at the dose of 2.63 mg/kg of the body mass for 6 weeks results in neurotoxicity to increase the relative refractory period of the caudal nerve [17].…”
mentioning
confidence: 99%
“…Insufficiency of antioxidant processes is confirmed by reduced levels of Cu/ZnSOD and TAS in blood serum. The study showed that neuronal membranes and astrocytes serve as target cells for the aqueous suspension of nanodispersed MnO, administered perorally or inhaled [7,10,12]. This can be explained by the pronounced ability of nanodispersed MnO, as well as other metals, to penetrate from the gastrointestinal tract into the blood.…”
mentioning
confidence: 99%
See 1 more Smart Citation